2020
DOI: 10.1039/d0cp00468e
|View full text |Cite
|
Sign up to set email alerts
|

The viscosity of dilute carbon nanotube (1D) and graphene oxide (2D) nanofluids

Abstract: The interpretation of viscosity facilitates the understanding of motion modes in liquid dispersions containing 1D and 2D nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…One explanation for the reduction in polymer viscosity could be that it is due to the presence of radical degeneration from the PG, which happens when produced radicals react with the polymer backbone, resulting in a reduction of molecular weight [37]. A study into the viscosity of graphene oxide nanoparticles dispersed in water however, did not observe the reduction of viscosity with an increase in graphene concentration [38]. The study concluded that the viscosity was due to particle concentration and temperature, and this suggests that the reduction in viscosity is due to the interaction of the PCL polymer backbone and PG.…”
Section: Characterisation Of Fibresmentioning
confidence: 99%
“…One explanation for the reduction in polymer viscosity could be that it is due to the presence of radical degeneration from the PG, which happens when produced radicals react with the polymer backbone, resulting in a reduction of molecular weight [37]. A study into the viscosity of graphene oxide nanoparticles dispersed in water however, did not observe the reduction of viscosity with an increase in graphene concentration [38]. The study concluded that the viscosity was due to particle concentration and temperature, and this suggests that the reduction in viscosity is due to the interaction of the PCL polymer backbone and PG.…”
Section: Characterisation Of Fibresmentioning
confidence: 99%
“…As the fullerene cluster size decreases the viscosity also decreases, which agrees with previous observations for oxide nanoparticles, carbon nanotubes, and graphene oxide. 26,27 The wear scars on the balls after friction tests (Figure S2a MO is widely used as a lubricant that can be enhanced with the addition of nanomaterials. The MO and nano oils (MO/ C 60/70 , MO/T2.5/C 60/70 , and MO/T25/C 60/70 ) were evaluated by the ball on disk method to understand their lubrication properties.…”
Section: Resultsmentioning
confidence: 99%
“…The fullerene powder used in this study contains a mixture of C 60 , C 70 , higher fullerenes, and carbon particles to use a product with a lower cost than a high-purity C 60 sample. The nanoparticle size and concentration have been reported to modify the viscosity of lubricants, , thus, it is necessary to estimate the fullerene cluster size, concentration, and C 60 /C 70 ratio in the MO/C 60/70 mixtures. Therefore, the MO/C 60/70 mixtures were characterized by high-performance liquid chromatography (HPLC) and dynamic light scattering (DLS) (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…% of metal oxides, and MWCNTs had an average diameter and length of 9.5 nm and 1.5 μm, respectively, according to the provider. The complete characterization of the solid, including elemental analysis and Raman spectrum, as well as its dispersion properties, have been previously published [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%